Adult Mouse Retina Explants: From ex vivo to in vivo Model of Central Nervous System Injuries - Schaeffer, Julia; Delpech, Céline; Albert, Floriane; Belin, Stephane; Nawabi, Homaira (Frontiers in Molecular Neuroscience, 2020)
In mammals, adult neurons fail to regenerate following any insult to adult central nervous system (CNS), which leads to a permanent and irreversible loss of motor and cognitive functions. For a long time, much effort has been deployed to uncover mechanisms of axon regeneration in the CNS. Although several molecular pathways, such as mTOR and JAK/STAT, have been identified as regulators of axon regeneration, no functional recovery has been achieved yet. Today, there is a need not only to identify new molecules implicated in adult CNS axon regeneration, but also to decipher the fine molecular mechanisms associated with regeneration failure. Here, we propose to use cultures of adult retina explants to study all molecular and cellular mechanisms that occur during CNS regeneration. We show that adult retinal explant cultures have the advantages to (i) recapitulate all the features observed in vivo, including axon regeneration induced by intrinsic factors, and (ii) be an ex vivo set-up with high accessibility and many downstream applications. Thanks to several examples, we demonstrate that adult explants can be used to address many questions, such as axon guidance, growth cone formation and cytoskeleton dynamics. Using laser guided ablation of a single axon, axonal injury can be performed at a single axon level, which allows to record early and late molecular events that occurs after the lesion. Our model is the ideal tool to study all molecular and cellular events that occur during CNS regeneration at a single-axon level, which is currently not doable in vivo. It is extremely valuable to address unanswered questions of neuroprotection and neuroregeneration in the context of CNS lesion and neurodegenerative diseases.